Peran Kelembagaan Perdesaan untuk Keberlanjutan Penerapan SRI di Kabupaten Karawang - Suciati, Luh Putu; Juanda, Bambang; Fauzi, Akhmad; Rustiadi, Ernan (Jurnal Ekonomi dan Pembangunan Indonesia, 2014)
Sustainability of System of Rice Intensification (SRI) requires rural institution role. The study was conducted in Karawang and uses institutional economics approach and logit regression. The analysis shows potential problems of SRI related with principal-agent/institutional relation and economics transaction costs. Strengthening the activities within farmer groups will reduce economics transaction costs in beginning of application. Farmer will choose "bagi hasil/revenue sharing" as land management cooperation with moderate risks and transaction costs. Monitoring and incentive mechanism will reduce problems of adverse selection and moral hazard. Some factors which determine the sustainability of SRI are production, principal position, off farm work and ex ante transaction costs.